Comparative study on the antifungal activity of chitosan of various origins tested in different conditions of radiation treatment and culture mediums - Lam, Nguyen Duy; Diep, Tran Bang (Academia Journal of Biology, 2015)
The antifungal activity of three chitosan samples varied in the molecular weights (280,000, 552,000 and 830,000 D) and in the origins of production (Vietnam and Japan) were studied against Fusarium dimerium Penzig. The liquid and agar-plate mediums were formulated for evaluating the minimal inhibitory concentration (MIC) and the sensitivity of culture method. For antifungal activity enhancement, chitosan samples were irradiated with gamma rays in solid and paste-like conditions. Results showed that the MIC of chitosan samples tested in liquid medium was above ten times smaller than that of chitosan samples tested on agar-plates. So the method using liquid medium had higher sensitivity than the agar-plate method. MICs of native chitosan samples using liquid medium ranged from 280 to 320 mg/L were independent on their molecular weight (MW). The radiation treatment in solid and paste-like conditions had improved the chitosan antifungal activity. In addition, there was a maximal activity appeared for each of chitosan samples that has been irradiated in any condition. For enhancement of maximal antifungal activity, the solid-state radiation treatment required dose of 50-100 kGy, while a lower range of doses could be used in case of treatment in paste-like state. Further more, the optimal radiation dose for maximal antifungal activity enhancement was recorded as the initial MW dependent: the higher MW of the initial chitosan required higher dose.